Key establishment protocols in mobile communication - Teo, Chee Khiang. (2008)
A variety of authenticated key establishment protocols for mobile applications had been proposed in recent years. One of the purposes of this research project is to examine and analyze some of the more prominent published authenticated key establishment protocols with regards to security and efficiency. In this research project, a number of goals pertaining to security in authentication process are identified and the authenticated key establishment protocols are then evaluated using these goals. In addition, the authenticated key establishment protocols are also simulated using known cryptosystems such as RSA and AES. Data from these simulations are then used to compare the efficiency of the various protocols. The authenticated key establishment protocols are then compared and further analyzed, particularly with regards to mobile efficiency. Generally, the more secured a key establishment protocol is, the more computational complex it is.